The Factors of Employee Performance: A Study of SearchNEasy - Teoh, Kok Ban; Cordova, Miguel; Hor, Sin Ni; Lim, Chung Hong; Yeoh, Li Khuan; Madhu, Amitha; Warrier, Uma; Chan, Jia Jun; Kee, Daisy Mui Hung; Tan, Florence E-Vern; Chia, Jia Xin; Chuah, Yan Jin (Asia Pacific Journal of Management and Education (APJME), 2021)
SearchNEasy is a Malaysia-based Web Development Company providing leading customized web solutions for worldwide business over the past 20 years. People, process, and technology are three elements for successful business transformation. The ongoing Covid-19 pandemic affects the workload of employees as the demand for the company's service for web design increases due to the Movement Control Order (MCO), where the Malaysian government commands the closure of all private and government sectors, except those deemed as essential needs. This research intends to understand the factors contributing to employees’ performance. This study was conducted through primary and secondary research with respondents and existing data. Through this study, employees’ performance, job stress, job demand, organizational culture, and organizational rewards were analyzed. It was shown that job stress is one of the factors of employee performance in SearchNEasy due to the increase in workload and lack of employees during the Covid-19 pandemic.